Dispersion of nano-silica in monomer casting nylon6 and its effect on the structure and properties of composites (eXPRESS Polymer Letters, 2010)
To promote dispersion of nano-silica in monomer casting nylon6 (MC nylon6), nano-silica was dispersed in melted caprolactam with the assistance of ultrasound, anionic polymerization was then initiated to form silica/MC nylon6 in-situ nanocomposites. It was found that hydrogen bonds were formed between nano-silica and caprolactam, in the meantime, ultrasound helped to break the nanoparticles aggregations into smaller ones or even mono-dispersing particles. Therefore, the agglomerated nanoparticles were pulled apart and stabilized by caprolactam. Additionally, the rapid anionic polymerization of caprolactam also contributed to the avoidance of re-agglomeration and deposition of nanoparticles during the polymerization process, leading to the uniform distribution of nanoparticles in the polymer matrix. Mechanical tests indicated that the silica/MC nylon6 in-situ nanocomposites prepared according to the above strategy were simultaneously toughened, strengthened and stiffened. Thermogravimetric analysis (TGA) results showed that thermal stability of nanocomposites was notably improved compared to neat MC nylon6.